AUDIT SUMBER DAYA MANUSIA TERHADAP KINERJA GURU DI SMK NEGERI 1 KEMLAGI MOJOKERTO - Kurniawan, Deni; Bhayangkara, I.B.K. (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTHuman resources are one of the important factors in increasing the ability of productivity to maintain and restore school probabilities. Schools must also pay attention to the level of teacher satisfaction so that teachers can work productively. The productivity of a school is influenced by various factors, one of the important factors is the quality of human resources owned. Began degan (recruitment) based on (job description). To determine the compensation that is given up to human resource maintenance activities (1) To find out and identify problems related to human resource management in the implementation of teacher performance appraisal in the State High School 1 Kemlagi Mojokerto (2) To find out the Role of HR Audit (human resources) in evaluating teacher performance at SMK Negeri 1 Kemlagi Mojokerto (3) Providing recommendations that might be used for HR function at SMK Negeri 1 Kemlagi Mojokerto. This research belongs to the type of evaluative research, and the suitable research approach is descriptive qualitative, which is supported by quantitative data collection through structured interviews or, questionnaires, observations and documentation (1) SMKN has not been maximized in providing facilities for the learning process to participants students (2) SMKN is still lacking in many shortcomings and weaknesses obtained from the findings to be improved (3) Not all the teaching material facilities have been fulfilled in the classroom. Keywords: Evaluation, Human Resources, Teacher Performance